Public R&D Policy: The Right Turns of the Wrong Screw? The Case of the German Biotechnology Industry - Andreas Fier; Oliver Heneric (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
The German biotechnology industry missed the accession of this key technology in the 1980s. Policy makers make different efforts to overcome shortcomings and recent gaps. Public funding schemes have been implemented to establish a flourish biotech industry in Germany. We assume that R&D policy was driven blind by the idea to catch up with world?s biotech leaders and analyse if Germany?s R&D policy lost its origins. We do examine, if Germany sacrifice economic funding principles, in particular not discriminating different kinds of ?risk? in the field of biotechnology. The study combines survey data of German biotech companies and public R&D funding data on the firm level. The results shed light on the factors which determine public R&D funding and firm?s probability of being funded.
Keywords: C21; L21; H32; M13; L65; O38; 330; Biotechnology; Public Policy; Innovation; Subsidies; Forschungs- und Technologiepolitik; Biotechnische Forschung; Innovationspolitik; Biotechnische Industrie; Schätzung; Deutschland